The Empowerment of Infaq and Waqf Evaluation in light of Maqasid al-Sharia Perspective in Mosques in Palangka Raya, Indonesia - Syaikhu, Syaikhu; Norwili, Norwili; Maimunah, Maimunah; wahyunita, laili (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
In a community in Indonesia, the proposal of establishing a mosque as the activity center has increasingly bloomed. This program restores the exuberance of the mosque through religious practices and places it as the center of community life in social, cultural, and economic aspects. In Palangka Raya, several mosques played an economic role in building bazaars around mosques, including bistros and other small businesses. Given that most of the mosques in the city have obtained large amounts of infaq (almsgiving) and waqf, it is essential to know the extent to which these funds are used in improving the economy of Muslims, especially in Palangka Raya and its surrounding area. The researchers used qualitative research by extracting primary data through interviews, observations, and documentation. This study aimed to evaluate the extent of empowerment of infaq and waqf in the mosques of Palangka Raya City in the maqasid al-shariaperspective. This study argued that the problems in the economic empowerment plan for mosques in Palangka Raya were the lack of human resources (HR), socialization, and funds. Therefore, to minimize the drawbacks, mosque management should continue to improve its quality by socializing mosque programs, providing training for new mosque cadres, and offering professional development for existing human resources on managing zakat, infaq, and sadaqah to maximize the mosque income.